Image processing for locating low back pain according to Thai traditional medicine. - ทวีแสงรุ่งโรจน์, วีรวัฒน์; Nuiden, Nida; Tandhavadhana , Sasithorn; Kongart, Chomlak (Science Technology and Innovation Journal, 2021)
This research is a study to determine the position of low back pain. By using image processing to analyze and assess the location of pain in the lower back to find the position of back pain according to Thai traditional medicine. It uses images of people suffering from lower back pain to process them as thermal images. And measure the temperature in each position. In order to take the data into consideration, it will be able to distinguish the back heat position, thus assessing the back pain position according to the Thai traditional medicine.